Probing for Congenital Nasolacrimal Duct Obstruction in Children Older than One Year Age - Safi, Abdul Basir; Rahimi, Ibrarullah (International Journal For Research In Applied And Natural Science, 2021)
Tear duct probing and irrigation is a procedure used in the treatment of nasolacrimal duct obstruction. The success rate of probing for congenital nasolacrimal duct obstruction in children older than 1 year of age Hospital based cross—sectional observational study. The study was performed in Nangarhar university teaching hospital within a seventh months study duration. A retrospective study was done of consecutive children undergoing probing for congenital nasolacrimal duct obstruction. The children who had bilateral Nasolacrimal obstruction, just one eye was included in the study. The study period was from 1stjune 2020 up-to 1stDecember 2020. A total of 56 children undergoing probing for congenital nasolacrimal duct obstruction. Right eye involvement was present in 22 (39.29%) cases and left eye in 34 (60.71%) cases. The children were divided into two groups. Group 1 (1 – 2 years) and group 2 (>2 years). The mean age of children in group I was 19.45 ± 3.68 months and in group ii. 32.71 ± 17.04 months. There were 42 male and 14 female children. The success rate in group I was 89.29% and in group II. 87.57%. failure was more in group II (21.43%) as compared to group I (10.71%). Probing is highly successful in the older age group (78.57%) and should remain the first line of treatment in older children.